Vertical jump assessment on volleyball: A follow-up of three seasons of a high-level volleyball team - Borràs, X.; Balius, X.; Drobnic, F.; Galilea, P. (The Journal of Strength and Conditioning Research, 2011)
This is a longitudinal descriptive study whose purpose is to assess the physical state of male volleyball players competing at the international level, comparing their jump heights during 3 different seasons. National team sample relies upon trainer decisions, and it was different every season. There were 23, 15, and 13 players in the first, second, and third years, respectively. Subjects underwent a vertical test protocol consisting of rocket jump, squat jump (SJ), countermovement jump (CMJ), CMJ with arms (CMJa), and spike jump (DJb) at the preparation period of the national team season. In 2007, an extra evaluation was performed during the competitive period. A contact mat was used for the assessment. An increase of jump height was observed over the years, with SJ and DJb increasing significantly (FSJ = 5.4; FDJb = 4.7; p < 0.05). The elasticity index decreased significantly between 2007 and 2008 (FEI = 8.5; p < 0.05), whereas arm utilization index and approach index increased, but this increase was not statistically significant. A significant increase in SJ and DJb was also observed between the 2 tests performed in 2007, whereas a nonsignificant increase was observed for CMJ and CMJa. The results indicate a better performance of explosive strength, elastic-explosive strength, and reflex-elastic-explosive strength and a better use of arms during jumps.